The feasibility of a modified shoe for multi-segment foot motion analysis: a preliminary study. Issue 1 (December 2016) - Halstead, J.; Keenan, A.; Chapman, G.; Redmond, A.
Abstract Background The majority of multi-segment kinematic foot studies have been limited to barefoot conditions, because shod conditions have the potential for confounding surface-mounted markers. The aim of this study was to investigate whether a shoe modified with a webbed upper can accommodate multi-segment foot marker sets without compromising kinematic measurements under barefoot and shod conditions. Methods Thirty participants (15 controls and 15 participants with midfoot pain) underwent gait analysis in two conditions; barefoot and wearing a shoe (shod) in a random order. The shod condition employed a modified shoe (rubber plimsoll) with a webbed upper, allowing skin mounted reflective markers to be visualised through slits in the webbed material. Three dimensional foot kinematics were captured using the Oxford multi-segment foot model whilst participants walked at a self-selected speed. Results The foot pain group showed greater hindfoot eversion and less hindfoot dorsiflexion than controls in the barefoot condition and these differences were maintained when measured in the shod condition. Differences between the foot pain and control participants were also observed for walking speed in the barefoot and in the shod conditions. No significant differences between foot pain and control groups were demonstrated at the forefoot in either condition. Conclusions Subtle differences between pain and control groups, which were found during barefoot walking are retained when wearing the modified shoe. The novel properties of the modified shoe offers a potential solution for the use of passive infrared based motion analysis for shod applications, for instance to investigate the kinematic effect of foot orthoses.